The distribution of lightning-caused forest fires in Quebec: 1978-1992. - Hurtubise, Paula. (University of Ottawa (Canada), 1996)
This study is more in the nature of "exploratory" than "confirmatory" in its exploration of the temporal and spatial patterns of lightning-caused forest fires in Quebec, for the fifteen year period 1978 to 1992. Economic returns garnered from forest products, as well as species and habitat loss, make lightning-caused forest fires an important area for investigation. Natural forest fires are affected by many factors. For the purposes of this study two classes of variables are used in the investigation of the location and timing of lightning forest fires; these are species and weather data. The species data is gathered at the zone forest level and forest age is used at a mature or young level. Weather variables are limited to temperature, precipitation and thunderstorms. These are selected as a result of agreement in related literature that they are valid variables to work with. Lightning-caused fires are mapped at various temporal scales and these are compared with the species and weather data. The study reveals a dichotomous relationship, where fuel characteristics, or forest species, determine the location of fires (or spatial component), and weather dominates the temporal component. Finally, an attempt was made to make generalisations based on the findings so as to identify issues for further research. Understanding the mechanisms which drive the occurrence and distribution of lightning-caused forest fires, is one of the first steps in creating lightning-caused forest fire models.
Keywords: Physical Geography.